Economic valuation of ecosystem service benefits for a proposed water regulation of ecosystem service payment for water in the basin of Jequetepeque, Peú - Portilla Claudio, Alfredo H. (2011)
Tesis (M. Sc) -- CATIE, Turrilba (Costa Rica), 2011